Análisis del Software Fotogramétrico Agisoft Metashape En la Solución a Problemas de Ingeniería e Infraestructura. - Guzman Zabala, Juan Francisco
This article is part of the theoretical basis from which the training processes to be taught in the geomatics room of the ´Centro de Tecnologías para la Construcción y la Madera´ (CTCM) will be developed, the aim will be to analyze and identify the main functions and tools of Agisoft MetaShape software and its contextualization in different areas of worldwide application. The above mentioned with the purpose of imparting knowledge about this new technology in technological programs of Topography, Construction, Civil Works and Graphic Development. Such training processes will focus on the post-process of aerial and terrestrial images for the construction of 3D digital models through Agisoft; adopting this software as an alternative that enriches the methods of conventional topography, with a view to positively incurring solutions related to engineering and infra-structure. In order to achieve the objective and purpose posed, the following workflow was structured: first, the basic and advanced functions of the software were identified; second, the state of the art was investigated, through different digital platforms and databases avai-lable at the institution; third, information was validated through technical meetings with companies in the pro-duction sector, which compiled the technical aspects discussed here and power in this way, to build a compara-tive analysis of the data.